Predictive Significance of Renal Histopathology as Correlated with Renal Function in Patients of Nephrotic Syndrome - Zaheer, Sufian; Sharma, Preeti; Aziz, Mehar; Haque, Shahzad F (Annals of Pathology and Laboratory Medicine, 2019)
Background: The advent of renal biopsy in early 1950’s has greatly enhanced the understanding of renal disease including nephrotic syndrome in all areas of clinical nephrology, pathology and investigations. The biopsy data, complemented by appropriate clinical, laboratory information and basic studies has contributed significantly to the body of knowledge of renal disease. Material and methods: This study was undertaken to analyze the usefulness of renal biopsy in patients of nephrotic syndrome. The present study was conducted on 52 patients of nephrotic syndrome, with detailed clinical examinations, relevant biochemical investigations and these patients were subjected to renal biopsy for detailed histopathological examination. Results: Of the 52 cases, 34 (65.4%) were male and 18 (34.6%) were females with male to female ratio of 1.9:1 and mean age being 29.5+ 12.5 years. Pre-biopsy clinical assessment revealed the major cause of nephrotic syndrome as primary glomerular disease in 42 (80.8%). Secondary cause of nephrotic syndrome was suspected in the remaining 10 (19.2%) of patients. After pathological evaluation, the major cause of nephrotic syndrome observed in the present study was primary glomerular diseases which accounted for 40 (76.9 %) patients. Secondary glomerular diseases were observed in the remaining 12 (23.1%) patients. Post biopsy histopathological diagnosis lead to change in therapy in 67.4% of the patients and the alteration of therapy post biopsy most commonly revolved around the use of corticosteroid. In 8 patients therapy with cytotoxic drugs was started. Conclusion: The estimate of prognosis was in agreement (pre-biopsy and post-biopsy) in 61.5 % of cases whereas in 20 (38.5%) patients it was different. In 12 (23.1%) cases a better prognosis was estimated and in 8 (15.4%) cases it was worse than estimated previously.